Technologies used by nursing to predict clinical deterioration in hospitalized adults: a scoping review - Érica Sobral Gondim; Emiliana Bezerra Gomes; José Hiago Feitosa de Matos; Sarah de Lima Pinto; Célida Juliana de Oliveira; Ana Maria Parente Garcia Alencar (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to map the early clinical deterioration technologies used in nurses' professional practice in the care of hospitalized adult patients. Methods: this is a scoping review, according to Joanna Briggs Institute Reviewer's Manual, which seeks to map the main technologies for detecting early clinical deterioration of hospitalized patients available for use by nurses, summarizing them and indicating gaps in knowledge to be investigated. Results: twenty-seven studies were found. The most present variables in the technologies were vital signs, urinary output, awareness and risk scales, clinical examination and nurses' judgment. The main outcomes were activation of rapid response teams, death, cardiac arrest and admission to critical care units. Final considerations: the study emphasizes the most accurate variables in patient clinical assessment, so that indicative signs of potential severity can be prioritized to guide health conducts aiming to intervene early in the face of ongoing clinical deterioration.